The Influence of Price Perception, Store Atmosphere, and Location on Purchasing Decisions at Alfar Banyudono Grocery Store - Setiana Kusuma; Heni Susilowati (Cahaya Abadi Publisher, 2025)
Technological and industrial developments have significantly impacted people's lives, particularly in the business world. The digitalization of services and the introduction of innovative solutions have facilitated faster and more efficient business growth, particularly in grocery stores. This study aims to explore the influence of price perception, store atmosphere, and location on purchasing decisions at Alfar Grocery Store. The study involved a total of 100 respondents, who are consumers of Alfar Grocery Store, with data collected using a non-probability sampling technique. The research method used is multiple linear regression analysis with quantitative research. The results show that price perception, store atmosphere, and location significantly influence purchasing decisions at Alfar Grocery Store. These three variables play a major role in shaping consumer decisions when shopping at the store. Based on these findings, the study provides recommendations for improving the shopping experience, such as enhancing the store's atmosphere to make it more comfortable for customers, providing updated price catalogs periodically to help buyers plan their purchases, and expanding parking facilities to ensure customer satisfaction with the store's location. Overall, this study emphasizes the importance of these factors in influencing consumer behavior and suggests that grocery stores, particularly Alfar Grocery Store, can improve sales and customer loyalty by addressing these key elements effectively.